2015
DOI: 10.1128/aem.01860-15
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of the Lactobacillus reuteri Glycoside Hydrolase Family 70 GTFB Type of 4,6-α-Glucanotransferase Enzymes That Synthesize Soluble Dietary Starch Fibers

Abstract: c 4,6-␣-Glucanotransferase (4,6-␣-GTase) enzymes, such as GTFB and GTFW of Lactobacillus reuteri strains, constitute a new reaction specificity in glycoside hydrolase family 70 (GH70) and are novel enzymes that convert starch or starch hydrolysates into isomalto/maltopolysaccharides (IMMPs). These IMMPs still have linear chains with some ␣1¡4 linkages but mostly (relatively long) linear chains with ␣1¡6 linkages and are soluble dietary starch fibers. 4,6-␣-GTase enzymes and their products have significant pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(94 citation statements)
references
References 48 publications
5
87
2
Order By: Relevance
“…Determination of the total activity of GtfC on amylose, in the absence or presence of 1 mM CaCl 2 , revealed that the Ca 2ϩ ions slightly activated GtfC enzyme activity, as is the case for L. reuteri 121 GtfB (20). The effects of pH and temperature on the activity of the full-length GtfC enzyme were examined with amylose V as a substrate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Determination of the total activity of GtfC on amylose, in the absence or presence of 1 mM CaCl 2 , revealed that the Ca 2ϩ ions slightly activated GtfC enzyme activity, as is the case for L. reuteri 121 GtfB (20). The effects of pH and temperature on the activity of the full-length GtfC enzyme were examined with amylose V as a substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the well-recognized I-to-IV homology regions, the three additional conserved regions (VI, V, and VII) proposed to be related to the maintenance of the structure and to a given enzyme specificity in GH13 family proteins (6,31,32) were identified in the GH70 and GH13 sequences. Interestingly, GtfC-and GtfB-like proteins had some Left, predicted GtfB domain organization plotted along the primary structure (20). Right, primary structure of the E. sibiricum GtfC protein showing functional regions identified by the Pfam server, annotated with information about the pairwise alignment of the different regions, the predicted domain order, and the locations of conserved regions I to IV in GtfC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…linkages, generating a linear chain with α-1,6 linkages (Bai et al, 2015;Leemhuis et al, 2014). This specific activity makes GTFB an interesting target enzyme for producing novel starches in planta.…”
Section: Introductionmentioning
confidence: 99%